The increasing of Human Resources quality Through Food Security in Semarang City (A Study of Legal Anthropology) - Handayani, Emy; Wicaksono, Satrio Adi (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
Development of food security has a strategic meaning in development in an area through its human resources, in accordance with Constitution number 18 of 2012 concerning food, that the provincial, district / city and / or village governments determine the type and amount of certain food reserves according to the consumption needs of the local community. The Human Development Index (HDI) also states that three factors determine the Human Development Index, namely education, health, and economy, so the quality of human resources is very influential and has an important role in developing and managing food so that a synergistic relationship between various aspects of the food security development in a region is needed. In this study, improving the quality of human resources in the city of Semarang in terms of the Anthropological Study of Law on food security, the method used through a normative juridical approach that is the law conceptualized as a normative symptom in legislation with the legal anthropological approach, the population in this study is the Department of Agriculture Semarang City with samples of food products in improving the quality of its human resources The results of this study comes through the Empirical Legal Anthropology approach, the support of strong and effective food institutions can spur growth, development and improvement of food, the nutritional status improvement of the community is very influential in improving the quality of human resources in increasing intelligence and the performance of human resources in determining future growth as one of strengthening local food security in the city of Semarang. With the availability of high quality human resources characterized by a strong physical, strong mental, excellent health and mastering science and technology can support the development of the city of Semarang.